Shaping the journalism education studies in Malaysia: The effects from the study on ethnicity [Membentuk pengajian kewartawanan di Malaysia: Kesan dari kajian etnik] - Arifin, Norizah; Ismail, Awan; Yusof, Norhafezah; Ismail, Rizalawati (School of Media and Communication Studies (MENTION), Faculty of Sciences and Humanities, University Kebangsaan Malaysia, 2015)

(untitled)
Journalism education is a unique field of study under a liberty of social science because it works in context. The surrounding society gives a lot of impact on how journalism has been practiced and educated. However, there are not many studies on journalism education that focuses on the elements of its society (i.e. gender, ethnic, religion, class, etc.), what more studies from the students’ perspectives. Therefore, this study attempts to fill the gap by having students of journalism as its samples. This article presents an extract from a huge study on journalism education in Malaysia. It studies the journalism students’ perceptions and expectations of journalism education in Malaysia and identifies whether different ethnics in Malaysia make any differences in their perceptions and expectations. Using quantitative methodology, 187 sets of survey questionnaires were collected from Malaysian journalism students who are studying at public universities in Malaysia. The result shows significant differences in terms of good journalism practice, news gathering skills and news production skills between three main ethnics of Malaysian journalism students.